2014
DOI: 10.3109/14992027.2014.921736
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the attitudes of practitioners toward teleaudiology

Abstract: Willingness to use teleaudiology depended on a combination of the clinical tasks to be performed and the patient populations to be served. These findings can help guide the successful implementation of teleaudiology services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
5
48
2
Order By: Relevance
“…A positive attitude by clinicians towards teleaudiology has been reported by others (Singh et al, 2014). However, in this study, whilst most reported a familiarity with telehealth and teleaudiology, and also a willingness to use telehealth for delivery audiology services, less than one quarter reported having used telehealth for consultations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A positive attitude by clinicians towards teleaudiology has been reported by others (Singh et al, 2014). However, in this study, whilst most reported a familiarity with telehealth and teleaudiology, and also a willingness to use telehealth for delivery audiology services, less than one quarter reported having used telehealth for consultations.…”
Section: Discussioncontrasting
confidence: 51%
“…The audiology profession around the world plays a key role in further developing this potential. A Canadian study of audiologists and other hearing health professionals has shown that the profession believes teleaudiology will have a minimal impact on the quality of client-practitioner interactions and hearing healthcare delivery (Singh, Pichora-Fuller, Malkowski, Boretzki, & Launer, 2014). However, the attitude and readiness of this community to incorporate it as part of current service-delivery frameworks has been largely unexplored especially from an international perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Work to date suggests that clinicians are open to using teleaudiology for answering patients' questions and for counseling; clinicians are moderately accepting of remote hearing aid adjustment and hearing screening but have reservations about using teleaudiology for hearing aid fittings and assessments, especially for new hearing aid users [13]. The patient perspective is somewhat more positive, with about 75 percent of patients being moderately to extremely willing to try teleaudiology.…”
Section: Figurementioning
confidence: 97%
“…The patient perspective is somewhat more positive, with about 75 percent of patients being moderately to extremely willing to try teleaudiology. Further, twothirds of clinicians and patients in a small industryfunded study became more positive about the use of teleaudiology after having engaged in its use [13].…”
Section: Figurementioning
confidence: 99%
“…Thus it is important to understand their attitudes toward tele-audiology, as done in the work of Singh et al (2014). Singh et al surveyed the attitudes of 202 hearing health-care practitioners toward tele-audiology appointments in general, their willingness to conduct specific audiological tasks via tele-audiology, and the use of tele-audiology appointments with different patient populations.…”
Section: Potential Barriers To Internet Usagementioning
confidence: 99%